Choosing a Contraceptive Method: What Matters to Women With Medical Conditions [17O]. (May 2016) - Mody, Sheila K.; Cansino, Catherine; Rible, Radhika; Steinauer, Jody; Harken, Tabetha
Abstract : INTRODUCTION: Factors that influence contraceptive initiation among women with complex medical conditions are unknown. METHODS: We conducted a cross-sectional study of women 18–45 years old with complex medical conditions who received contraception consultation from family planning specialists at 5 University of California Medical Centers. We asked patients about factors important in initiating a method. RESULTS: Among 97 recruited participants, medical conditions fell into these categories: neurologic (37%), endocrine (37%), cardiovascular (21%), rheumatologic (12%), oncologic (6%), and other (29%), and 10% had a history of a solid organ transplant, 7% bariatric surgery, and 6% venous thromboembolism. A majority of participants initiated long-acting, reversible contraceptive (LARC) methods including a progestin intrauterine device (IUD, 40.0%), the copper IUD (14.7%) and the contraceptive implant (17.9%). The most common reason for initiating contraception was to avoid pregnancy in the immediate future for personal reasons (45.3%). The most common reason for initiating a particular contraceptive method was safety given their medical condition (20.2%). Women commonly reported that the person with the most influence on their contraceptive method choice was the family planning specialist (37.2%) and medical condition specialist (22.3%), and less commonly the primary care provider (9.6%) and a family member or friend (12.8%). CONCLUSION: This study provides insight into contraceptive decision-making among women with medical conditions. When these women are given specialized contraceptive counseling they often choose highly effective methods.